TEACHING AND LEARNING FOREIGN LANGUAGES IN UZBEKISTAN CEFR: LEARNING, TEACHING AND ASSESSMENT - Hakimova, Gulnigor ("Science Shine" International scientific journal, 2024)
The Common European Framework of Reference (CEFR) is the most comprehensive, and the most widely used set of foreign language education standards throughout the world. The recent reforms in foreign language teaching in Uzbekistan have mainly touched upon teaching English language in all levels and stages of education. At this point CEFR plays as the main framework to be adopted in developing the national standard. In this article, we shall discuss reforms of adoption and implementation of the new standard which was a requirement of time and has started a new era in the whole system of foreign languages learning in Uzbekistan.